The Role of Flame–flow Interactions on Lean Premixed Lifted Flame Stabilization in a Low Swirl Flow. Issue 5 (4th April 2023) - Shahsavari, Mohammad; Farshchi, Mohammad; Arabnejad, Mohammad Hossein; Wang, Bing
ABSTRACT: Swirling flows have been widely used to stabilize lean premixed combustion in various gas turbines and furnaces. In such flows, understanding and characterizing the flame stabilization are of both practical and fundamental interests. It is known that the swirling motion decreases the flow velocity at the burner outlet, which contributes to flame stabilization. In low swirl flows, such a deceleration stabilizes a premixed flame aerodynamically. The present investigations, using large eddy simulations, study flame–flow interactions in lean premixed lifted flame stabilized in a low swirl flow. The results show that in addition to the swirling motion, combustion heat release reduces axial velocity in the reactant stream by reducing dilatation, vortex stretching, and baroclinic vorticity production terms. The analyses of vorticity production source terms show that besides the flow deceleration induced by the swirling motion, the dominant mechanism for the flow deceleration upstream of the low swirl lifted flame is the baroclinic torque. However, unlike the dilatation term, the effects of the vortex stretching and baroclinic diminish further upstream of the flame front.